Testing Mediation Disclosure Of GHG On The Relationship Between Corporate Governance And Firms’ Value - Susbiyani, Arik; Animah, Animah (Universitas Muhammadiyah Malang, 2024)
Purpose: The aim of this research is to examine the mediating effect of disclosure of GHG on the relationship between corporate governance represented by independent commissioners, board of directors, and management ownership on firm value Methodology/approach: The research uses panel data from the annual reports of manufacturing companies listed on the IDX from 2020 to 2022 totaling 114 data. Findings: This result shows that Corporate governance contributes positively to disclosure of GHG and firm’s value. Disclosure of GHG can improve a firm's value when the role of independent commissioners and managerial ownership mechanisms are effective in controlling the management. However, the board of directors does not contribute to firm’s value. Practical implications: These findings can motivate companies to optimize the environment by utilizing environmentally friendly technology that has added value, namely by the actions of reusing, reducing and restoring. Managers who care about green investment will be more open in disclosing GHG so that they get a good response from stakeholders Originality/value: There are still limited research references regarding corporate governance on company value mediated by disclosure of GHG. This research develops previous research by exploring modified GHG disclosure in a mediation model.